MANDIBULAR OSTEOMA, ARISING FROM A MENTAL SPINE - A CASE REPORT - Petia Pechalova; Tanya Sbirkov; Deyan Neychev; Elena Poriazova (Peytchinski Publishing, 2017)
The osteoma is a benign osteogenic neoplasm. It consists of well- differentiated compact or cancellous bone. The prevalence of osteomas in the normal population is about 4 %. Osteomas may be classified as peripheral, central or extraskeletal. Peripheral osteomas occur not commonly in jawbones. It affectsore frequently mandible than maxilla, and the most common sites are the angle and lower border of the body. The aim of this article is to present a rare case of peripheral osteoma, arising from a mental spine. 77 years old women, was reffered in our department with complaints of hard, nonpainful spike under her tongue, which hinder stability of her dentures during the eating and speaking. A traditional radiography was made. A surgical removal of formation was performed. The diagnose was established after the pathohistological examination was made. No complications were noted during the observed 6 months post surgery period.